Immediate autologous breast reconstruction after neoadjuvant chemoradiotherapy for breast cancer: initial results of the first 29 patients. Issue 3 (24th September 2017) - Grinsell, Damien; Pitcher, Meron; Wong, Shirley; Guerrieri, Mario; Nielsen, Hans H. M.
Abstract : Background: Breast reconstruction after mastectomy in the treatment of locally advanced breast cancer is often done in stages and before radiotherapy. We have previously published an algorithm for immediate free autologous reconstruction after neoadjuvant chemotherapy and preoperative radiotherapy. This protocol was designed to provide a shorter and simpler reconstructive path whilst improving cosmesis and maintaining oncological efficiency. Methods: A total of 29 patients were included and underwent surgery for 30 cancers by the first author between 2010 and September 2015. Data were prospectively entered into a database and analysed for tumour size, chemotherapeutic response, lymph node involvement, surgical complications and tumour recurrence. Results: The mean age was 55 ± 7 years. Eighty percent of patients had either a partial or complete chemotherapeutic response defined as >25% decrease in tumour size. Twenty‐eight patients had free abdominal tissue transfer. One patient was excluded due to advanced disease. There were no take‐backs due to microsurgical issues. One patient was reoperated on for a haematoma. Four patients had recurrent cancer during follow‐up, three of whom are deceased. Conclusion: Many, but not all, breast reconstructive surgeons consider autologous reconstruction as the 'gold' standard in the presence of radiotherapy. Rearranging the order of radiotherapy and surgery means operating in a recently irradiated field. We believe the surgical challenges are outweighed by a shorter and simpler reconstructive journey that additionally results in a better cosmesis. It is possible to perform immediate free autologous reconstruction after neoadjuvant chemotherapy and preoperative radiotherapy with excellent results and at least equivalent oncological efficacy.